Effect of low-level laser therapy in the treatment of temporomandibular disorder: Case report (Research, Society and Development, 2021)
Temporomandibular disorder (TMD) is a multifactorial pathology characterized, in most cases, by pain conditions that affect the temporomandibular joint and / or the orofacial muscles. There are several conservative therapeutic modalities, including low-level laser therapy or LLLT, which are used successfully for the management of TMD. The aim of this study was to report the case of a patient with temporomandibular disorder of muscular origin whose therapeutic approach was laser therapy and psychological monitoring. The selected patient was submitted to a 12-session laser therapy protocol with an AsGaAl diode laser (808 nm, 80mW, 120J / cm², continuous). The RDC / TMD axis I and II instrument was used to initially assess the patient. The variables: maximum mouth opening (measured in mm) and pain (mediated by the Visual Analogue Scale (VAS) 0-10; 0 with no pain and 10 with maximum pain) were analyzed during the sessions and at the end of treatment. According to the evaluation by EVA, there was a reduction in pain from 8 (pre-irradiation) to 1 (post-irradiation), and an improvement in mouth opening of 4mm. There was a positive result regarding the decrease in myofascial pain and improvement in the opening of the mouth due to the dysfunction presented by the patient. Therefore, laser therapy is a viable option in the control of TMD of muscular origin.